Rho‐kinase inhibitor Y‐27632 increases cellular proliferation and migration in human foreskin fibroblast cells. Issue 17 (15th June 2015) - Piltti, Juha; Varjosalo, Markku; Qu, Chengjuan; Häyrinen, Jukka; Lammi, Mikko J.
<x xml:space="preserve">Abstract</x> The idea of direct differentiation of somatic cells into other differentiated cell types has attracted a great interest recently. Rho‐kinase inhibitor Y‐27632 (ROCKi) is a potential drug molecule, which has been reported to support the gene expressions typical for the chondrocytes, thus restricting their phenotypic conversion to fibroblastic cells upon the cellular expansion. In this study, we have investigated the short‐term biological responses of ROCKi to human primary foreskin fibroblasts. The fibroblast cells were exposed to 1 and 10 μM ROCKi treatments. A proteomics analysis revealed expression changes of 56 proteins, and a further protein pathway analysis suggested their association with the cell morphology, the organization, and the increased cellular movement and the proliferation. These functional responses were confirmed by a Cell‐IQ time‐lapse imaging analysis. Rho‐kinase inhibitor treatment increased the cellular proliferation up to twofold during the first 12 h, and a wound model based migration assay showed 50% faster filling of the mechanically generated wound area. Additionally, significantly less vinculin‐associated focal adhesions were present in the ROCKi‐treated cells. Despite the marked changes in the cell behavior, ROCKi was not able to induce the expression of the chondrocyte‐specific genes, such as procollagen α1(II) and aggrecan.